(untitled) (Vietnam Journal of Community Medicine, 2024)
Objective: To analyze a number of factors related to the results of care for patients with neurological bladder due to spinal cord injury at the Rehabilitation Center, Bach Mai Hospital in 2022. Subject and method: Cross-sectional description of 133 patients aged 18 years and older, diagnosed with neuromuscular bladder treatment at the Rehabilitation Center, Bach Mai Hospital. Results: The rate of poor care in patients with spinal cord injuries with neurological bladder was 18% and this rate was higher in retired patients compared to other occupations (38.9% compared to 14.8%); patients with upper-secondary school education compared to lower-secondary school (23.8% compared to 9.4%); in patients who have not achieved dietary care compared to patients (38.9% compared to 14.8%) and patients who have not achieved respiratory care compared to patients who achieved respiratory care (41.2% compared to 14.7%). Conclusion: The incidence of poor care in patients with spinal cord injury with neurobladder in the study was 18%. Some factors related to poor care are: patients with qualifications below upper secondary school, patients who have not retired, patients who have not received care in terms of eating and breathing.